2014
DOI: 10.1111/twec.12222
|View full text |Cite
|
Sign up to set email alerts
|

Export Experience of Managers and the Internationalisation of Firms

Abstract: As the firm gravitates toward being the core in analyses of international trade, the possibilities for learning from cross‐disciplines studies increase. Managerial resources underlie export initiation in the theory of the multinational enterprise developed in international business studies, but they are largely ignored in empirical studies of international trade. This is probably not because they are unimportant, but more due to the challenges of identifying and measuring these resources. We exploit Danish emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Previous export experience among workers and managers has been found to be among the key determinants of export entry decisions, export status and trade intensity for Portuguese firms (Mion and Opromolla 2014). Similarly, Sala and Yalcin (2014) and Minondo (2011) show that hiring managers with previous export experience is positively associated with a firm's likelihood of foreign market entry, based on micro data from Denmark and Spain and probit or linear probability models.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous export experience among workers and managers has been found to be among the key determinants of export entry decisions, export status and trade intensity for Portuguese firms (Mion and Opromolla 2014). Similarly, Sala and Yalcin (2014) and Minondo (2011) show that hiring managers with previous export experience is positively associated with a firm's likelihood of foreign market entry, based on micro data from Denmark and Spain and probit or linear probability models.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Only a limited number of studies have used representative firm-level datasets to estimate its contribution in determining export decisions (e.g. Sala and Yalcin 2014;Mion and Opromolla 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While it is consolidated that productivity determines firms' selection into exporting, recent hypotheses have started to investigate more closely the deliberate efforts undertaken by firms to become exporters (conscious self-selection). Some studies have explored technological investments or quality upgrading (Alvarez and Lopez, 2005; Iacovone and Javorcik, 2012), while other studies have focused on human capital investments with firms building up the right expertise in preparation for exporting (Sala and Yalcin, 2012;Molina and Muendler, 2013). Our paper identifies the diversity of the workforce as a driver of internationalization, which 4 …”
Section: Creative Decisions May Be Lost To the Increased Communicatiomentioning
confidence: 99%
“…CEOs' global orientation and technological background, therefore, have positive (+) effects on internationalisation [37,39]. Kuemmerle [40] and Sala and Yalcin [41] have also suggested that a significant relationship exists between entrepreneurial characteristics such as global orientation and the speed or level of internationalisation. This association is due to CEOs' abilities to be able to reduce the cultural and psychological barriers, and we would like to define these abilities as global orientation.…”
Section: Relationships Among Technological Characteristics Ceos' Glomentioning
confidence: 99%
“…Sala and Yalcin [41] also argued that entrepreneurs' global orientation were able to determine the level and pattern of internationalisation of INVs. Furthermore, in a study of 335 SMEs in Norway, Moen [24] found a significant relationship between CEOs' global orientation and the pace of internationalisation.…”
Section: Relationships Among Technological Characteristics Ceos' Glomentioning
confidence: 99%